2024
DOI: 10.1177/14034948231219832
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems among adolescents during the COVID-19 pandemic: a repeated cross-sectional study from Sweden

Håkan Källmen,
Mats Hallgren

Abstract: Objective: Most international studies have concluded that exposure to the COVID-19 pandemic was associated with worse mental health. Sweden implemented lighter restrictions than many other countries. We evaluated the association between changes in exposure of COVID-19 restrictions and changes in mental health problems among Swedish adolescents. Method: Repeated cross-sectional data were derived from the Stockholm school survey, mandatory for all students in municipal schools and voluntary for students in priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The conflicting findings between these Swedish studies are fascinating yet challenging to explain. One possible explanation could be that the different studies [42,43] examined only limited aspects of mental health, focusing on anxiety and various worry themes as well as depression and somatic complaints [27]. In contrast, the current study conceptualises mental health in a broader sense, encompassing symptoms of anxiety, depression, loneli-ness, anger, and involvement in conflict.…”
Section: Changes In Mental Health During the Covid-19 Pandemicmentioning
confidence: 82%
See 1 more Smart Citation
“…The conflicting findings between these Swedish studies are fascinating yet challenging to explain. One possible explanation could be that the different studies [42,43] examined only limited aspects of mental health, focusing on anxiety and various worry themes as well as depression and somatic complaints [27]. In contrast, the current study conceptualises mental health in a broader sense, encompassing symptoms of anxiety, depression, loneli-ness, anger, and involvement in conflict.…”
Section: Changes In Mental Health During the Covid-19 Pandemicmentioning
confidence: 82%
“…This finding is noteworthy because a previous review [41] and a study focused on the same population [28] in a multinational context showed a higher increase in mental health issues among young women. In the context of Swedish adolescents, several studies demonstrated that adolescent women reported experiencing poorer mental health outcomes such as headaches, depression, feeling fear, stomach problems, difficulty sleeping, poor appetite, and increased anxiety and worry levels after exposure to COVID-19 compared to adolescent men [27,42,43].…”
Section: Changes In Mental Health During the Covid-19 Pandemicmentioning
confidence: 99%
“…In the study by Hafstad et al, somatic health complaints were shown to increase ahead of and 15 months into the pandemic whereof girls appeared to be more affected than boys [19]. Other studies also report a more adverse effect on mental health in girls compared to boys [17,21,22]. Most studies published concerning the COVID-19 pandemic's effect on adolescents have been based on cross-sectional data not being able to shed light on the longitudinal effects within the same group of individuals.…”
Section: Introductionmentioning
confidence: 96%